Diagnostic Yield of Dental Radiography and Cone-Beam Computed Tomography for the Identification of Anatomic Structures in Cats - Heney, Colleen M.; Arzi, Boaz; Kass, Philip H.; Hatcher, David C.; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2019)
The objective of this study was to evaluate the diagnostic yield of dental radiography (DR) and 3 cone-beam computed tomography (CBCT) methods for the identification of predefined anatomic structures in cats. For 5 feline cadaver heads and 22 client-owned cats admitted for evaluation and treatment of dental disease, a total of 22 predefined anatomic structures were evaluated separately by use of the DR method and 3 CBCT software modules [multiplanar reconstructions (MPR), tridimensional (3-D) rendering, and reconstructed panoramic views (Pano)]. A semi quantitative scoring system was used, and mean scores were calculated for each anatomic structure and imaging method. The Friedman test was used to evaluate values for significant differences in diagnostic yield. For values that were significant the Wilcoxon signed rank test was used with the Bonferroni-Holm multiple comparison adjustment to determine significant differences among each of the possible pairs of diagnostic methods. Differences of diagnostic yield among the DR and 3 CBCT methods were significant for 17 of 22 anatomic structures. For these structures, DR scores were significantly higher than scores for Pano views for 2 of 17 structures, but DR scores were significantly lower than scores for Pano views for 6 anatomic structures, tridimensional rendering for 10 anatomic structures, and MPR for 17 anatomic structures. In conclusion, it was found that CBCT methods were better suited than DR for the identification of anatomic structures in cats. Results of this study can serve as a basis for CBCT evaluation of dentoalveolar and other maxillofacial bony lesions in cats.